Polemik Keberadaan Izin Tinggal Terbatas Investor Terhadap Keamanan Nasional Republik Indonesia - Eiunike Aurora Shafia Putri; Ni Wayan Rainy Priadarsini (Kertha Wicaksana, 2025)
The increasing number of foreigners in Indonesian territory is inseparable from the ease of access permitted by the local government. The lack of border control and the ease of travel in and out of the country can lead to various national security threats such as the threat narcotics smuggling, illegal foreign workers, to the proliferation of fraudulent companies that harm the countryF. Immigration plays a pivotal role in maintaining the sovereignty of the Republic of Indonesia, particularly through the functions of immigration supervision and enforcement. On the other hand, to maintain national security, the state must still open foreign investment to fulfil national interests that cannot be pursued single-handedly. The existence of foreign investors is supported by the Directorate General of Immigration by issuing limited stay permits (ITAS) while they are in Indonesia. This journal will highlight how the role of supervision and screening will be carried out by Immigration, especially the Immigration Office Class I TPI Denpasar against foreign investors who own limited stay permit cards on the island of Bali. This research uses a qualitative approach with primary data sources from interviews and state document studies as well as secondary data from several articles and journals. The results of the analysis found that although access to foreigners is facilitated, the Directorate General of Immigration is also increasingly aggressively disciplining ITAS holders of investors so that they are not misused by routinely carrying out foreigner surveillance operations throughout Indonesia, especially Bali, to catch foreigners whose activities are not in accordance with the applicable residence permit.